Euthanasia Dalam Tinjauan Aspek Hak Asasi Manusia - tri susilowati (Fakultas Hukum Universitas Darul Ulum, 2016)
With the development in the field of medicine, is not impossible to contain the thorny and complex issue which through knowledge and medical technology is very current, diagnosis of a disease can be more perfect, more immediate treatment can penyakitpun eefektif. With modern medical equipment, then the pain a person can diperingann seseorangpun life can be extended for a certain period of time by installing a